2011
DOI: 10.1353/hpu.2011.0074
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sociocultural Factors on Colonoscopy and FOBT Screening Adherence among Low-income Hispanics

Abstract: Few studies have examined barriers and facilitators to colorectal cancer (CRC) screening among Hispanics, particularly sociocultural factors that may be relevant. This paper examines the influence of sociocultural factors on adherence to fecal occult blood testing (FOBT) and colonoscopy. A survey was conducted among a sample of 400 low-income Hispanics in East Harlem, New York. Fatalism and health literacy were both significantly associated with colonoscopy screening adherence in bivariate models, though fatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
58
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 57 publications
8
58
1
Order By: Relevance
“…Fatalistic beliefs have been associated with lower utilization of screening for early detection of other malignancies such as breast [36–38], colorectal [39,40], and cervical cancer [41,42]. Similarly, other studies have found an association between fear and anxiety related to the procedure and underutilization of colonoscopy and Pap smears [43–45].…”
Section: Discussionmentioning
confidence: 99%
“…Fatalistic beliefs have been associated with lower utilization of screening for early detection of other malignancies such as breast [36–38], colorectal [39,40], and cervical cancer [41,42]. Similarly, other studies have found an association between fear and anxiety related to the procedure and underutilization of colonoscopy and Pap smears [43–45].…”
Section: Discussionmentioning
confidence: 99%
“…CRC information requires a wide range of literacy skills that cover basic concepts of health to more advanced concepts of risk probability and statistics (Schapira et al, 2014). Low health literacy has been found to be a barrier to CRC screening in prior research (Kobayashi, Wardle, & von Wagner, 2014; Shelton, Jandorf, Ellison, Villagra, & DuHamel, 2011) and is associated with less CRC awareness, CRC test knowledge, CRC screening test efficacy, and negative attitudes toward fecal occult blood test [FOBT] (Arnold et al, 2012; Dolan et al, 2004). In addition, low health literacy has been associated with less confidence in obtaining a stool blood test and CRC screening completion (Arnold et al, 2012).…”
mentioning
confidence: 99%
“…Persistent disparities in CRC screening exist between Hispanic and non-Hispanic white males [24]. Many disparities result from economic barriers to care such as health insurance status, as well as fear and mistrust of medical care [7,8]. Thus, tailored interventions based on patient navigation may be effective in improving adherence to clinical preventive guidelines and health care outcomes [7,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research work on CRC screening for Hispanics suggests that interventions targeting this population must go beyond improving access to care or socioeconomic status [4,5]. Rather, a promising avenue of intervention for Hispanics may be through a better understanding of group-specific behavioral and cultural factors that are likely to influence CRC screening (e.g., fear of medical encounters, stigma of lower endoscopy, and low levels of health literacy) [6][7][8]. There is already some evidence in the literature about the utility of patient navigation to improve CRC screening by targeting these behavioral and cultural factors [9].…”
Section: Introductionmentioning
confidence: 99%